Adaptive Web-Based Information System for MBKM Program Using Scrum - Putri, Riska; -, Okta; khairunisa, farinnadiya; -, Cristopher; Nababan, Marlince (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2025)
The implementation of the “Merdeka Belajar Kampus Merdeka” (MBKM) program requires an integrated and adaptive information system to manage academic activities efficiently. This study aims to develop a web-based MBKM Management Information System at Universitas Prima Indonesia using the Scrum framework. The system supports structured registration, reporting, assessment, and verification processes involving students, academic advisors, department heads, and MBKM administrators. Technologies used include React.js and Next.js for the frontend, Express.js for the backend, and MySQL for the database. A key contribution of this research is the application of the agile Scrum methodology to accommodate the dynamic nature of MBKM policies, ensuring iterative development and user-centered design. Internal testing using Black Box methods indicates high functionality and usability. The resulting system enhances efficiency, data integration, and stakeholder collaboration. This study demonstrates how agile practices can be effectively applied to develop scalable academic systems that support national education reforms.